Facilitated Communication Denies People With Disabilities Their Voice. (September 2014) - Travers, Jason C.; Tincani, Matt J.; Lang, Russell
Facilitated Communication (FC) has been rebranded as "supported typing" and repackaged as rapid prompting method, but remains a disproven intervention for people with disabilities. Despite the absence of supportive evidence and abundant evidence that facilitators always author the messages, FC has experienced resurgence in popularity among families, professionals, and advocacy groups. Strategic marketing, confirmation bias, pseudoscience, anti-science, and fallacy explain this troubling renewal. We briefly discuss each of these and contrast the method with authentic augmentative and alternative communication to illustrate differences in values and practices. Our intention is to persuade readers to resist or abandon FC in favor of validated methods and to encourage advocacy organizations to advance agendas that emphasize genuine self-expression by people with disabilities.